Effects of short-term consumption of strawberry powder on select parameters of vascular health in adolescent males. Issue 1 (16th January 2020) - Holt, Roberta R.; Zuelch, Michelle L.; Charoenwoodhipong, Prae; Al-Dashti, Yousef A.; Hackman, Robert M.; Keen, Carl L.
Abstract : In both children and adults, dietary interventions strongly supports the concept that the regular consumption of strawberries can be associated with improvements in cardiovascular health. Abstract : Cardiovascular disease is a leading cause of death in the United States and much of the developed world, costing billions of dollars in lost work time, lower productivity and high health care expenditures. Research on foods and bioactive food components that have cardioprotective benefits may provide new insights as to how modest changes in one's diet may result in a reduced risk of vascular disease. In intervention trials, the consumption of strawberries, either fresh or freeze-dried, has been reported to improve select markers of cardiovascular health, including improved lipid profiles, microvascular function, and platelet reactivity. Consistent with the above, epidemiological studies suggest beneficial effects of strawberries on vascular function. Preliminary studies on the effects of freeze-dried strawberry powder on vascular health are reviewed in the current paper.